NHC-based diazo compounds: pathways to N2 liberation or dimerization - Balayan, Kajal; Tiwari, Prabhakar; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Journal of Organic Chemistry, 2026)
We previously reported the C-H bond cleavage of Me3SiCHN2 by 1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene (5-SIPr) to form 1. In this article, we showed that electron-poor diamido carbene 5-tBuDAC also cleaves the C-H bond of Me3SiCHN2 to form 5, unlike its ring-expanded congener 6-DippDAC, which forms N-heterocyclic methylene hydrazine. The divergence of reactivity has been explained with the help of DFT studies. Further divergence occurs when 1 and 5 were reacted with HCl. While dimerization was observed with 5-SIPr based diazoalkane to give quinoidal tetrazine (2), N2 elimination occurs from 5-tBuDAC based diazoalkane to afford 7 and 8. This contrasting behavior highlights the subtle yet profound influence of the N-heterocyclic carbene (NHC) framework on the fate of the diazo units. DFT studies shed light about the mechanism for the formation of 2 as well as reveal that N2 elimination is thermodynamically favored over dimerization for 5.